Effect of Irrigation Water pH on the Performance of Healthy and Huanglongbing-affected Citrus - Lushan Ghimire; Davie Kadyampakeni; Tripti Vashisth (Journal of the American Society for Horticultural Science, 2020)
Huanglongbing [HLB (Candidatus Liberibacter asiaticus)] is one of the most devastating diseases in citrus (Citrus sp.). Field observations in Florida have shown that citrus groves with high soil and irrigation water pH decline rapidly under HLB-prevalent conditions. It is worth noting that irrigation water pH has always been high in Florida; however, neither tree decline nor low productivity under such conditions has been an issue for citrus before HLB. Therefore, there is a need to determine if HLB increases citrus tree sensitivity to high-pH irrigation water. The objective of this research was to evaluate the molecular and physiological responses of healthy and HLB-affected citrus trees irrigated with water at pH levels of 5.8, 7.0, and 8.0. The results demonstrated that soil pH is positively correlated with irrigation water pH. Overall, regardless of disease occurrence, tree performance decreased as pH increased. HLB-affected trees at pH 8.0 had the greatest mortality (40%) and leaf drop (87%) and the lowest height growth (<1%) and leaf biomass (0.1 g). In contrast, HLB-affected trees at pH 5.8 had the lowest mortality (0%) and leaf drop (16%) and the greatest height growth (6.6%) and leaf biomass (5.5 g). Growth and survival data indicate that high pH had a less negative impact on healthy trees than HLB-affected trees, and that HLB symptoms were exacerbated at pH 8.0 compared with pH 5.8. A transcriptomic analysis of root tissue conducted at the end of the experiment further suggested that HLB-affected trees at pH 5.8 were actively detoxing stress-induced radicals and had increased growth and developmental processes with the downregulation of jasmonic acid biosynthesis compared with healthy trees. This implies that at pH 5.8, HLB-affected trees were under less stress than healthy trees. Compared with healthy trees, HLB-affected trees at pH 8.0 resulted in upregulated immune system processes, defense responses, and cell death; no processes were significantly downregulated in HLB-affected trees compared with healthy trees at pH 8.0. Physiological and molecular observations suggest an interaction between HLB and irrigation water pH whereby HLB symptoms are exacerbated in response to high irrigation water pH.